PENGARUH FOREIGN DIRECT INVESTMENT DAN AFTA TERHADAP KESEMPATAN KERJA SEKTORAL DI ASEAN 5 (Jurnal Ekonomi dan Kebijakan Pembangunan, 2015)
This study aims to analyze the impact of Foreign Direct Investment (FDI) ‎and ‎ASEAN Free Trade Agreement (AFTA) on sectoral employment in ASEAN ‎‎5. The analysis ‎focused on five main sectors, namely agriculture, mining, ‎manufacturing, ‎construction and service sectors. This paper uses panel data ‎approach with Fixed Effect Model. Variable used include employment as an ‎edogenous variable, while GDP, wages and AFTA as exogenous variables. Cross section data that are used in this study consist of ASEAN 5 countries, ‎namely Indonesia, Malaysia, Philippines, Thailand and Vietnam with periods of ‎observation as much as 9 years, from  2006 until 2014.‎The result of this paper that FDI, GDP, wages and AFTA have different ‎impacts in each sector. FDI has positive impact on employment in service sector. ‎GDP has positive impact on employment in manufacturing, construction and ‎service sectors. While GDP in the agricultural and mining sectors has negative ‎impact on employment. The wage has a positive impact on employment in the ‎mining and agricultural sectors. ASEAN Free Trade Agreement (AFTA) that took ‎place in 2010 has a positive impact on employment in the manufacturing and ‎mining sectors.‎Foreign Direct Investment is one factor to overcome employment issues in ‎ASEAN 5, especially in service sector. While GDP becomes an important variable ‎in enhancing ASEAN 5  employment in the manufacturing, construction and ‎services. Increasing wages can be applied on agriculture and mining as it has a ‎positive impact on employment. AFTA that has taken place is proper policy for the ‎ASEAN 5 to encourage economic growth in the mining and manufacturing ‎sectors that have an impact on increasing demand of labor in the sector.‎